2022
DOI: 10.1097/mao.0000000000003770
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Symptom Reporting for Benign Paroxysmal Positional Vertigo in a Traumatic Brain Injury Population

Abstract: ObjectiveTo assess the prevalence of benign paroxysmal positional vertigo (BPPV) in traumatic brain injury population.Study DesignIn this cross-sectional design, each subject completed screening for BPPV, which included subjective questioning and positional testing. Subjects were asked if they experienced dizziness with bed mobility. All were tested with the Dix-Hallpike and the roll test to determine if nystagmus consistent with BPPV was present.SettingBrain injury inpatient rehabilitation unit.ParticipantsSu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…By contrast, in a cross-sectional study of TBI subjects admitted to a rehabilitation unit, Harrel et al examined all 73 cases for BPPV without enquiring about the dizziness and found that 60% of the patients tested positive for BPPV despite only 10% of the total cohort having a subjective sensation of dizziness. 12 One explanation for the subjective versus objective discrepancy between studies might relate to the recently characterized TBI phenomenon of “vestibular agnosia” in which brain-injured patients have an obtunded sensation of vertigo. In this regard, Calzolari et al found that acute TBI patients with vestibular agnosia and BPPV were 7 times less likely to be referred for treatment than BPPV patients without vestibular agnosia.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in a cross-sectional study of TBI subjects admitted to a rehabilitation unit, Harrel et al examined all 73 cases for BPPV without enquiring about the dizziness and found that 60% of the patients tested positive for BPPV despite only 10% of the total cohort having a subjective sensation of dizziness. 12 One explanation for the subjective versus objective discrepancy between studies might relate to the recently characterized TBI phenomenon of “vestibular agnosia” in which brain-injured patients have an obtunded sensation of vertigo. In this regard, Calzolari et al found that acute TBI patients with vestibular agnosia and BPPV were 7 times less likely to be referred for treatment than BPPV patients without vestibular agnosia.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, symptomatic screening for BPPV found 6% BPPV rates 38 versus 58% obtained by examination in moderate-to-severe TBI survivors in a rehabilitation setting, of whom less than 10% had vertigo symptoms. 39 We previously showed that vestibular agnosia is linked to disrupted central brain circuits, 13 40 which in turn is linked to TBI severity. Thus, differences in cohort TBI severity affect vestibular agnosia rates.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Our recent work, followed by above reports in the elderly, showed the first evidence of vestibular agnosia in TBI, which explains the lack of concordance in symptoms and vestibular function observed previously. 3,8,9 Despite higher prevalence of BPPV, the TBI patients, 7,16 same as elderly individuals, 11,17,18 have fewer dizziness complaints due to VA. [11][12][13]17 Hence, we predict that using subjective report of symptoms and not accounting for VA, will inaccurately track vestibular dysfunction in TBI. For example, BPPV prevalence in similar in-patient rehabilitation TBI cohorts found prevalence of 7% 19 based upon screening via symptoms (dizziness) versus a 58% BPPV prevalence 16 based upon a systematic examination irrespective of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…3,8,9 Despite higher prevalence of BPPV, the TBI patients, 7,16 same as elderly individuals, 11,17,18 have fewer dizziness complaints due to VA. [11][12][13]17 Hence, we predict that using subjective report of symptoms and not accounting for VA, will inaccurately track vestibular dysfunction in TBI. For example, BPPV prevalence in similar in-patient rehabilitation TBI cohorts found prevalence of 7% 19 based upon screening via symptoms (dizziness) versus a 58% BPPV prevalence 16 based upon a systematic examination irrespective of symptoms. Thus, subjective symptom scores underdiagnose vestibular conditions in TBI cohorts.…”
Section: Introductionmentioning
confidence: 99%